Islam without a veil Kazakhstan's path of moderation - Salhani, Claude (Washington, D.C. : Potomac Books, 2011)
Examines the religious and political foundations of modern day Kazakhstan and argues that the country should serve as an example for other Muslim nations to live peacefully with citizens and international neighbors alike.
Preface -- Islam without a veil -- Islamophobia -- Kazakhstan emerges -- The new end game in Central Asia -- The "Kazakhi" way: economy first, politics second -- Shaking things up -- The road to moderation -- Islam and modernization -- The Kazakhstan experiment -- The terror threat and reasons for concern -- Kazakhstan's role in shaping Central Asia -- Can democracy and Islam co-exist? -- A conversation with a salafi -- Is a Middle East and Central Asia economic common market possible? -- Changin' times -- Conclusion.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Islam -- Kazakhstan; Kazakhstan -- Religion; Kazakhstan -- Economic conditions -- 1991-; Kazakhstan -- Social conditions -- 1991-; Islam -- Kazakhstan; Kazakhstan -- Religion; Kazakhstan -- Economic conditions; Kazakhstan -- Social conditions; RELIGION / Fundamentalism; RELIGION / Islam / History; Electronic books